Study Team on the Machinery for Planning Final Report - Administrative Reforms Commission (Administrative Reforms Commission, Government of India)
The Planning Process in India has been evolving as a result of improved understanding of planning techniques, the experience gained during the last 17 years, and evaluation, internal and external, of planning as it has worked in India up to now. It is obvious that planning has to be suited to the political, economic and social conditions and the stage of economic development reached in a given country, and the techniques suited to one country cannot necessarily be transplanted to another one.